2014
DOI: 10.1189/jlb.3a1013-541r
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase 2 promotes sepsis-associated lethality by facilitating production of interleukin-27

Abstract: The aim of this study was to test the hypothesis that gene expression and release of IL-27 may be modulated by Tyk2. Macrophages derived from the peritoneum or bone marrow of C57BL/10SnJ (WT) mice produced abundant amounts of IL-27(p28) following TLR4 activation by LPS. In contrast, production of IL-27(p28), but not EBI3, was reduced by ∼50% in TLR4-activated macrophages derived from mice with genetic deficiency of Tyk2 compared with WT macrophages. Frequencies of IL-27(p28)+F4/80+CD11b+ cells were lower in TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 49 publications
4
24
0
Order By: Relevance
“…We have recently shown that IL-27RA -/- mice have improved survival rates during endotoxic shock (46). IL-27(p28) production during endotoxic shock and polymicrobial sepsis induced by CLP is partly dependent on tyrosine kinase 2 via an autocrine type I interferon loop (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that IL-27RA -/- mice have improved survival rates during endotoxic shock (46). IL-27(p28) production during endotoxic shock and polymicrobial sepsis induced by CLP is partly dependent on tyrosine kinase 2 via an autocrine type I interferon loop (46).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that IL-27RA -/- mice have improved survival rates during endotoxic shock (46). IL-27(p28) production during endotoxic shock and polymicrobial sepsis induced by CLP is partly dependent on tyrosine kinase 2 via an autocrine type I interferon loop (46). Our finding that F4/80 + CD11b + macrophages derived from IL-27RA -/- mice displayed increased ROS production after stimulation with opsonized E. coli is consistent with similar findings in LPS-stimulated phagocytes derived from EBI3 -/- mice (12).…”
Section: Discussionmentioning
confidence: 99%
“…Both Toll/IL-1R domain-containing adaptor inducing IFN-b and MyD88 adaptor proteins are required for IL-27p28 production in LPS-activated macrophages (9,18,19). Tyrosine kinase 2 specifically promotes the gene expression of IL-27p28 rather than EBI3 following TLR4 activation (20). The downstream signaling pathways involve recruitment of IFN regulatory factors 1, 3, and 9 and NF-kB (c-Rel) transcription factors to the promoter region of the IL-27p28 gene (18,19,21).…”
Section: Neuroendocrine Modulation Of Il-27 In Macrophagesmentioning
confidence: 99%
“…The downstream signaling pathways involve recruitment of IFN regulatory factors 1, 3, and 9 and NF-kB (c-Rel) transcription factors to the promoter region of the IL-27p28 gene (18,19,21). Additionally, IL-27 production is greatly amplified by type I and type II IFNs based on autocrine/ paracrine-positive feedback loops (20,21). Alternatively, PI3K/ Akt and STAT3 represent inhibitory signaling pathways for antagonizing IL-27p28 gene expression in LPS/TLR4-activated macrophages (9,16).…”
Section: Neuroendocrine Modulation Of Il-27 In Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation